COGNITIVE RESPONSE ON FAVORITE PLACE CASE STUDY OF INDONESIAN YOUNG ADULTS - Finta Lissimia (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2020)
ABSTRACT Environmental behavior studies discuss the relationship between environment and the behavior of its users, namely humans. The human response to the physical character of the environment is divided into invisible and visible aspects. Cognitive aspects are invisible response that rarely got attention. Meanwhile, place preference study may result in desirable physical setting. The embodiment of place preferences is a favorite place. Favorite place is a place with higher preference for each person. This article will discuss cognitive responses on favorite place so the result can complement the knowledge about response-based design. Finding cognitive response on favorite place can be achieved using quantitative methods. The data then analyzed using distribution, analysis of variance (ANOVA) and factor analysis. The respondents are Indonesian young adults aged 18-40 years old. The most favorite place of this age group are culinary place, urban commercial, and marine tourism objects. Meanwhile cognitive response that arise on favorite place are hospitality and togetherness. There are five latent variables of cognitive that is environmental experience, social affordance, ecological quality, personal interests, and urban quality Keywords: cognitive response; environmental behavior; favorite place